A comparative study of haemocytes in three cyclorrhaphous dipteran flies. (15th August 2014) - Pal, Ruchita; Kumar, Krishna
<x content-type="archive" xml:space="preserve">Abstract</x> The larval haemolymph of three cyclorrhaphous dipteran flies, Sarcophaga ruficornis Fab., Musca domestica L. and Chrysomya megacephala Fab., possesses five different types of haemocytes: prohaemocytes; plasmatocytes; granulocytes; spherulocytes; oenocytoids. In addition, vermicytes are found in the haemolymph of S.ruficornis and adipohaemocytes in the haemolymph of M. domestica. The total haemocyte counts in the three dipteran flies show an increasing trend throughout the larval stage, attaining a peak value in the freshly formed white puparium stage and declining thereafter. The differential haemocyte count shows a decline in the number of prohaemocytes with an increase in the number of plasmatocytes, granulocytes and spherulocytes.